The Achieved Body (An Outlook on the Poetry of Vassilis Michaelides) - Vassileiou, Costas (Études helléniques / Hellenic Studies, 2014)
The poet Kostas Vasileiou, who has more sytematically written poetry in the Cypriot dialect in recent years, tries to highlight the best moments of Vassilis Michaelidis’s poetry, namely his nine best poems, written entirely in the Cypriot dialect, and doesn’t hesitate to place next to the best known ones the poem entitled «Amoloïtos» (The Unspoken) and the satirical “Romios” (The Greek).